Robust yet flexible slippery layered composite surfaces with a programmable pressure-resistance response under extreme environmental conditions. Issue 28 (29th June 2022) - Che, Pengda; Han, Xiao; Guo, Pu; Wang, Xuan; Cheng, Shuman; Han, Keyu; Jiang, Lei; Heng, Liping
Abstract : We present a universal strategy to produce robust yet flexible layered slippery surfaces. Based on these surfaces, the fabricated sensors possess outstanding stability in extreme working environments. Abstract : Flexible pressure sensors offering stable operation in harsh environments are in high demand, such as large pressure detection, submerged sensing, and detection in extremely low-temperature environments. However, deterioration of the functions of the component interfacial materials under severe conditions leads to poorer sensitivity, lifetimes, and reliability. To overcome these challenges, we report high-performance slippery surfaces with mechanical robustness and excellent flexibility by virtue of ordered arrangements of two-dimensional nanosheets in polydimethylsiloxane (PDMS) gel. Through reasonably tuning the types of lubricants and nanosheets, the slippery layered composite surfaces exhibit excellent mechanical properties (ultrahigh tensile strength of 235.9 ± 14.7 MPa, super-strong anti-compressive strength of 675.1 ± 32.9 MPa, and superb bending flexibility of 2874 ± 153 times) and superior liquid repellency whether at room temperature or at low temperature (down to −65 °C). In particular, the fabricated wearable sensors using the slippery layered composite surfaces exhibit not only excellent durability (10 000 cycles at 300 kPa pressure, or 2600 cycles under 90° bending), but also remarkable stability under harsh environmental conditions, including high pressure (320 kPa), ultra-low temperature (−65 °C), high humidity (95% RH), and under liquids (water, sweat, ionic liquid and N, N -dimethylformamide solvent). It is believed that the development of slippery layered composite surfaces with high mechanical performance provides new prospects for sophisticated wearable electronic devices.